2005
DOI: 10.1124/jpet.105.094326
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Type 2 Diabetes on Acetaminophen-Induced Hepatotoxicity in Male Swiss-Webster Mice

Abstract: Type 2 diabetic (DB) mice exposed to CCl 4 (LD 50 ϭ 1.25 ml/kg), acetaminophen (LD 80 ϭ 600 mg/kg; APAP), and bromobenzene (LD 80 ϭ 0.5 ml/kg) i.p. yielded 30, 20, and 20% mortality, respectively, indicating hepatotoxic resistance. Male SwissWebster mice were made diabetic by feeding high fat and administrating streptozotocin (120 mg/kg i.p.) on day 60. On day 71, time-course studies after APAP (600 mg/kg) treatment revealed identical initial liver injury in non-DB and DB mice, which progressed only in non-DB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…However, these investigations have shown conflicting results. Indeed, whereas some studies showed increased hepatotoxicity (Corcoran and Wong, 1987;Kon et al, 2010;Kučera et al, 2012), others demonstrated no difference or an obvious protection (Blouin et al, 1987;Ito et al, 2006;Sawant et al, 2006). Although the exact reasons for this discrepancy are currently unknown, several hypotheses can be put forward.…”
Section: Introductionmentioning
confidence: 99%
“…However, these investigations have shown conflicting results. Indeed, whereas some studies showed increased hepatotoxicity (Corcoran and Wong, 1987;Kon et al, 2010;Kučera et al, 2012), others demonstrated no difference or an obvious protection (Blouin et al, 1987;Ito et al, 2006;Sawant et al, 2006). Although the exact reasons for this discrepancy are currently unknown, several hypotheses can be put forward.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, in type 2 diabetic patients, contradictory evidence of increased CPY2E1 (Wang et al, 2003) and unchanged CYP2E1 protein and activity has been reported. Collectively, Sawant et al (2006) suggest are unlikely to explain diabetes-induced protection from APAP-induced hepatotoxicity.…”
Section: Effects Of Diabetes On Apap-induced Hepatorenal Toxicitymentioning
confidence: 92%
“…In STZ-induced type 1 diabetic rats, liver microsomal CYP2E1 protein expression and enzyme activity are markedly increased (Sakuma et al, 2001;Wang et al, 2000), whereas in type 1 diabetic (Sakuma et al, 2001;Shankar et al, 2003a). In type 2 diabetic rats (Sawant et al, 2004) and mice (Sawant et al, 2006) including type 2 ob/ob mice and Zucker rats (Novak and Woodcroft, 2000), CYP2E1 protein and mRNA are not significantly changed. In this connection, in type 2 diabetic patients, contradictory evidence of increased CPY2E1 (Wang et al, 2003) and unchanged CYP2E1 protein and activity has been reported.…”
Section: Effects Of Diabetes On Apap-induced Hepatorenal Toxicitymentioning
confidence: 99%
See 2 more Smart Citations